COMBINATION THERAPY USING A LIV1-ADC AND A CHEMOTHERAPEUTIC - SUSSMAN DJANGO; LI FU; KOSTIC ANA (2018)
The invention provides methods of treating a subject having or at risk of cancer by administering a LIV-1 antibody drug conjugate and a chemotherapeutic. 本发明提供通过施用LIV-1抗体药物偶联物和化学治疗来医治患有或处于癌症风险的受试者的方法。